Perceptions about penis size among supposedly healthy 40 to 60-year-old Brazilian men: a cross-sectional pilot study - Reis, Margareth de Mello Ferreira dos (2015)
CONTEXT AND OBJECTIVE: Many men seek medical treatments complaining that their penises are too small (short) when in fact they are not (they are not cases of micropenis). The objective of the present study was to evaluate men’s satisfaction with their own bodies and sex life and the prevalence of erectile dysfunction, among men who were not seeking medical or psychological advice. DESIGN AND SETTING: Cross-sectional study in a private, philanthropic hospital in São Paulo, Brazil. METHODS: In this study, 300 male blood donors aged between 40 and 60 years old answered a question-naire, in privacy, about their sex life and their satisfaction with their own bodies. They were also screened for erectile dysfunction by means of the International Index of Erectile Function questionnaire. RESULTS: Seven men (2.3%) reported that they were dissatisfied with their penis size (they thought that it was small), and among these, one was found to have mild erectile dysfunction. However, none of them had sought medical attention. Among these seven, only two had normal body mass index; the other five were overweight (three) or obese (two). CONCLUSION: The prevalence of dissatisfaction with penis size was low. Among the seven dissatisfied men, only one had erectile dysfunction, of mild type, and all of them felt potent.